Pelatihan Fotografi (Motrek) Bagi Guru SMP Dalam Upaya Revitalisasi Bahasa Daerah Untuk Tunas Bahasa Ibu di Balai Bahasa Provinsi Bali - I Nyoman Agus Suarya Putra; Aniek Suryanti Kusuma; Ayu Gede Willdahlia; Desak Dwi Utami Putra; I Ketut Sutarwiyasa; Putu Satria Udyana Putra; Ni Wayan Wardani; Ni Made Mila Rosa Desmayani; Putu Gede Surya Cipta Nugraha; Eddy Hartono; Gede Surya Mahendra (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2022)
The declining use of the Balinese language, especially among the younger generation, is something that the Bali Provincial Language Center needs to pay attention to immediately holding a language revitalization program. One of the activities in the regional language revitalization program is a photography training activity (motrek) for junior high school teachers which aims to revitalize language starting from the school realm, namely teachers and students. His hope in everyday life is not far from photography. The resulting photos can be given a description in Balinese, especially when uploading to social media. The training lasted for 4 days, attended by 75 State Middle School teachers. The training was filled with delivery of material, discussions, questions and answers and hands-on practice using each participant's cell phone. The results of the posttest showed an increase in understanding of the material by 48% from the results of the previous pretest.